Designing ternary quantum-dot cellular automata logic circuits based upon an alternative model. (October 2018) - Mohammadi Mohaghegh, Saman; Sabbaghi-Nadooshan, Reza; Mohammadi, Majid
Highlights: An alternative model for implementing ternary QCA logic circuits is demonstrated. This model is based upon the electron-electron interactions, energy calculations in ternary cells and can effectively solve the problems of ternary logic QCAs structures. Using the proposed model, some basic and combinational ternary circuits are designed and investigated while the final aim is to design ternary half adder by using various ternary gates. To ascertain our model capability in digital circuits, all the proposed designs are simulated with our newly designed TQCAsim software. The results show that, in addition to proper characterization, designed circuits are conveniently applicable for digital systems. Abstract: Three-valued logic is recently being considered in the field of multi-valued logic due to its competitive advantages over binary logic for development of state-of-the-art digital systems. Despite several advances in this area, a comprehensive model that could have a profound impact on the trend of such a newfound system has so far not been proposed. Therefore, this study is an attempt to design basic ternary Quantum-dot Cellular Automata logic gates and various combinational ternary circuits like adders by use of our proposed model. To verify the design circuits, proposed ternary logic circuits are simulated by newly designed TQCAsim software while to scrutinize the effectiveness of simulation method, some prior proposed conventional gates have also been simulated. Moreover, effective factors such as area, energy consumption, fault tolerant and cost are investigated in the proposed circuits. The results show that, in addition to proper characterization, designed circuits are conveniently applicable for digital systems.